Pengaruh Pemberian Tepung Kunyit yang Dicampur Dalam Air Minum Terhadap Pertambahan Bobot Badan, Konsumsi Pakan, dan Konversi Pakan Ayam Broiler - Arta S. Kasse; Charles V. Lisnahan; Oktovianus R. Nahak (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2021)
The purpose of this research was to know the effect of adding turmeric powder in drinking water on body weight gain, feed consumption, and feed conversion of broilers. This research was carried out in the Poultry Housing of Animal Science Study Program, Faculty of Agriculture, Timor University, Kefamenanu from Mei until July 2021. This research using 96 day old chick (DOC) broilers. The method used is Completely Randomized Design (CRD) consists of 4 treatments and 4 replication. The treatment was giving of T0: 1000 ml of drinking water (without turmeric powder), T1: 995 ml drinking water + turmeric powder 5 g, T2: 990 ml drinking water + turmeric powder 10 g, T3: 885 ml drinking water + turmeric powder 15 g. Data is processed using analysis of variance, and Duncan test. Statistical analysis shows that addition turmeric powder in drinking water significant effect weight gain, feed consumption and feed conversion of broilers (P<0.05). It was concluded that adding turmeric powder in drinking water give results the optimum of body weight gain, feed consumption and feed conversion of broilers.